Numerical and Experimental Investigations of Modal Coherence Characteristics for the Determination of Broadband Noise in Flow Ducts - Xu, Kunbo; Liu, Cunliang; Tong, Fan; Qiao, Weiyang (Frontiers in Energy Research, 2022)
This paper presents a numerical and an experimental investigations in detail about modal coherence charac-teristics of turbomachinery noise. The modal coherence characteristics of ducted noise at high frequencies are investigated by establishing three kinds of ducted sound source distribution models. The results are consistent with the acoustic experimental results of a single-stage axial fan. The results show that acoustic modes of dif-ferent orders are mutually incoherent, and radial modes within the same circumferential mode have a great de-gree of coherence. This paper successfully conducted acoustic measurement on turbomachinery noise by rotat-ing microphone arrays. The acoustic experimental results show that the coherence of some modes has little impact on the measurement of incident acoustic waves in the flow duct, while it leads to about 3dB deviation in the prediction of reflected modal sound power and has little influence on the spectral shape of reflected acoustic waves. It was demonstrated that the experimentally measured modal coherence functions give inner sense of the spatial noise source distribution and enable the investigation of mode scattering within the propagation. Based on the modal coherence characteristics obtained in this paper, more theoretical and methodological re-search can be carried out for the turbomachinery broadband noise test.